ANALYSIS ON TEACHERS' DIFFICULTIES IN ASSESSING STUDENTS’ ATTITUDES IN ONLINE CLASS - Rismawati, Rismawati; Ismu Purwaningsih, Dewi (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2024)
This study aimed to find out attitude assessments carried out by English subject teachers at West Pontianak Private Senior High Schools and to find out difficulties faced by English language teachers in developing attitude assessments at West Pontianak Private Senior High Schools. This research method used a qualitative descriptive approach. The research subjects were English Subject Teachers, with Classroom Teachers of class X and Counseling Guidance Teachers as support. Data collection techniques were interviews and documentation. The results of this study indicated that 12 teacher used observation techniques which include the assessment of spiritual attitudes and assessment of social attitudes in carrying out the assessment of student attitudes during the online learning period. There were 3 difficulties experienced by the teachers (1) There is no direct interaction (face to face) between educators and students (2) Not all students have android phones as a means of supporting the continuity of online learning (3) Difficulty in developing attitude assessment criteria, namely the responsibility of students to the tasks given by the teacher, discipline will collect assignments on time and obey school rules, namely by not leaving class (absence).